2021
DOI: 10.3390/en14185786
|View full text |Cite
|
Sign up to set email alerts
|

Energy Monitoring in the Wild: Platform Development and Lessons Learned from a Real-World Demonstrator

Abstract: This paper presents the development and evaluation of EnnerSpectrum, a platform for electricity monitoring. The development was motivated by a gap between academic, fully custom-made monitoring solutions and commercial proprietary monitoring approaches. EnnerSpectrum is composed of two main entities, the back end, and the Gateway. The back end is a server comprised of flexible entities that can be configured to different monitoring scenarios. The Gateway interacts with equipment at a site that cannot interact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…If smart meter failed to read or send the readings to the controller for more than 60 s, controller sent an alert notification message. Several privacy and security standards described in [36], and the proposed prototype system uses HTTPS for secure data tra 7, it is found that in the monsoon season, the proposed RMSSO algorithm completed 100% of the task (10 kW), while the SSO and SSA techniques completed 129.5% and 126.5%, respectively. In the same scenario, the percentage cost difference of SSO and SSA from RMSSO was 24.44% and 21.92%, respectively.…”
Section: System Architecturementioning
confidence: 98%
See 2 more Smart Citations
“…If smart meter failed to read or send the readings to the controller for more than 60 s, controller sent an alert notification message. Several privacy and security standards described in [36], and the proposed prototype system uses HTTPS for secure data tra 7, it is found that in the monsoon season, the proposed RMSSO algorithm completed 100% of the task (10 kW), while the SSO and SSA techniques completed 129.5% and 126.5%, respectively. In the same scenario, the percentage cost difference of SSO and SSA from RMSSO was 24.44% and 21.92%, respectively.…”
Section: System Architecturementioning
confidence: 98%
“…If the smart meter failed to read or send the readings to the controller for more than 60 s, the controller sent an alert notification message. Several privacy and security standards are described in [36], and the proposed prototype system uses HTTPS for secure data transmission between local databases and cloud storage. The controller uploaded all collected data as a CSV file to the cloud storage (Thingspeak).…”
Section: System Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…The house consumption standard scenario (Figure 3) considers a 4 MWh single-family house consumption from real data collected on Madeira Island [12], reflecting the average electricity consumption patterns in the Azores. In terms of PV generation (Figure 4), the default scenario reflects a 2.2 kWp PV system in the S. Miguel Island (~2000 sunshine hours per year).…”
Section: Case Studymentioning
confidence: 99%